Terpenoids and their gene regulatory networks in Opisthopappus taihangensis ‘Taihang Mingzhu’ as detected by transcriptome and metabolome analyses - Liu, Hua; Chen, Wendan; Chai, Yuhong; Liu, Wenchao; Chen, Haixia; Sun, Lei; Tang, Xiaowei; Luo, Chang; Chen, Dongliang; Cheng, Xi; Wang, Fengjun; Yuan, Xiaohuan; et al. (Frontiers in Plant Science, 2022)
‘Taihang Mingzhu’ is the hybrid offspring of Opisthopappus taihangensis , and it has an excellent characteristic of whole-plant fragrance. At present, the genes and metabolites involved in the synthesis of its aromatic compounds are unknown because of the paucity of molecular biology studies on flowering in the Opisthopappus Shih genus. To elucidate the biosynthetic pathways of terpenoids, the main aromatic compounds in ‘Taihang Mingzhu’, we conducted transcriptome and metabolite analyses on its leaves and inflorescences at the bud, color-development, flowering, and full-bloom stages. A total of 82,463 unigenes were obtained, of which 43,692 were annotated on the basis of information at the protein databases Nr, SwissProt, KEGG, and COG/KOG (e-value<0.00001). Using gas headspace solid-phase microextraction chromatography – mass spectrometry (HS-SPME-GC/MS), 1350 metabolites were identified, the most abundant of which were terpenoids (302 metabolites). Analyses of the gene regulatory network of terpenoids in ‘Taihang Mingzhu’ identified 52 genes potentially involved in the regulation of terpenoid synthesis. The correlations between genes related to terpenoid metabolism/regulation and metabolite abundance were analyzed. We also extracted the essential oil from the leaves of ‘Taihang Mingzhu’ by hydrodistillation, and obtained 270 aromatic compounds. Again, the most abundant class was terpenoids. These results provide guidance for the extraction of essential oil from ‘Taihang Mingzhu’ leaves and flowers. In addition, our findings provide a theoretical platform for further research on ‘Taihang Mingzhu’, and identify genetic targets to manipulate the aromatic profiles of this plant and other members the Opisthopappus Shih genus by molecular breeding.